Fabric, paleomagnetism, and interpretation of pre-illinoian diamictons and paleosols on Cloudy Ridge and Milk River Ridge, Alberta and Montana - Karlstrom, Eric; Barendregt, Rene (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractPebble fabrics and sedimentological properties indicate that pre-Wisconsinan diamictons (Kennedy Drift) on Cloudy Ridge (Alberta) and Milk River Ridge (Montana) are of glacial rather than colluvial origin. S1 and S3 eigenvalues of the upper units on the two ridges are typical of undeformed lodgement till whereas those of the lower unit on Milk River Ridge are typical of glacigenic sediment flow. Other properties, including compact matrices, striations on stones, mean pebble dip angles, and Schmidt equal-area stereonet patterns, suggest each unit is lodgement or basal till. Pedogenic features indicate weathering zones capping the tills are paleosols. Degree of rubification, clay, iron and aluminum buildup, and clay mineral alteration resembles those of very strongly developed soils formed in warmer and moister environments. The argument that “soil-like features” of the Cloudy Ridge unit resulted from post-burial diagenesis is disproven because nearly identical paleosols occur at the surface on Milk River Ridge and other interfluves to the south. Each unit examined has normal polarity. Based on comparisons with similar till/paleosol sequences exposed in Kennedy Drift sections on nearby interfluves, the Cloudy Ridge till and the upper till on Milk River Ridge were probably deposited during the early to middle Bruhnes Normal Chron (780 ka to present) whereas the lower till on Milk River Ridge is of earlier Brunhes age or dates back to the Olduvai (1.98 to 1.76 Ma) Normal Subchron or the Gauss Normal Chron (3.6 to 2.6 Ma).